ANALISIS KESESUAIAN LAHAN UNTUK TANAMAN KELAPA SAWIT DI WILAYAH GAMBUT DESA MEKAR SARI KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR - Intan S, Mas; Ardiansyah, Andri Noor; Windarti, Anissa (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
This study aims to determine the land suitability class for oil palm plantations in the peat area of Mekar Sari Village, Pasir Sakti District, East Lampung Regency. The research method used is a survey method with a quantitative approach. The population is the entire peat area of Mekar Sari Village. Sampling using technique puprposive sampling. Sampling was carried out according to the results of the unit map which is a combination of several maps, namely geological maps, soil types, slope and land use. Data collection techniques include primary and secondary data resulting from field observations and laboratory tests, the soil is analyzed using the methods scoring (grading) with addition/subtraction techniques. The results showed that land sample 1, land sample 2, land sample 3, land sample 4, land sample 5, land sample 6, land sample 7, and land sample 8 fall into the S1 class category (very suitable).